KERJASAMA BADAN NASIONAL PENANGGULANGAN TERORISME (BNPT) DAN UNITED NATIONS OFFICE ON DRUGS AND CRIME (UNODC) DALAM MENCEGAH DAN MENANGGULANGI KEJAHATAN TERORISME DI INDONESIA TAHUN 2018-2020 - Alfia Kusuma, (2023)
This study aims to look at the implementation and results of the cooperation between the Government of Indonesia through the National Counter-Terrorism Agency (BNPT) with the United Nations Office on Drugs and Crime (UNODC) in preventing and tackling terrorism crimes in Indonesia in 2018-2020. Theories and concepts used in this research are transnational crime, international organization and cooperation security. In this study the author describe the dynamics of prevention and countermeasures against terrorism, explain how the two institutions cooperate with each other and take a role in efforts to overcome terrorism crimes, especially in Indonesia, as well as the challenges and opportunities faced by BNPT and UNODC in an effort to support the Indonesian government in dealing with the problem of terrorism. The research method used is descriptive qualitative using data sources, namely primary data and secondary data. The primary data collection technique is sourced from interviews with related institutions and secondary data, namely in the form of data results obtained through published data, data that can be accessed easily and can be accessed by the general public such as through journal articles and results from research conducted been done by previous researchers. The final results of this study show that the cooperation between BNPT and UNODC in preventing and tackling terrorism crimes in Indonesia in 2018-2020 has shown success, this is demonstrated through the support provided by UNODC to Indonesia through capacity building, the involvement of BNPT and UNODC in the GUYUB Project , and the launch of a political declaration to support the handling of children involved in terrorism crimes. Even though at the end of 2019 the covid-19 pandemic emerged, the cooperation continued even with the existing adjustments and changes.